Characterization of instructional materials in environmental education for preschool children - Galvez, Farah Esperanza R. (2005)
Environmental Education (EE) can be learned at a very young age. This research was conducted to identify the characteristics of EE instructional materials that are effective in developing pro-environmental attitudes and behaviors in preschool children ages 3-5 years. The results indicated that effective instructional materials have: picture storybooks with a dialogue or a short narration; poster, cartoon videos and game boards with a single EE theme; class experiments that make use of common everyday things; short contests; setups of live animals and plants; and easy-to-do home activities. Change in the children's behaviors observed from the beinning to the end of the study manifested their growing concern for the environment.
"May 2005."
Thesis (M.A. Environmental Education)--University of the Philippines, Diliman.
Keywords: Environmental education -- Philippines; Preschool children -- Philippines; Teaching -- Philippines -- Aids and devices